Systematic Review on the Impact of Guidelines Adherence on Antibiotic Prescription in Respiratory Infections - Inês Oliveira; Catarina Rego; Guilherme Semedo; Daniel Gomes; Adolfo Figueiras; Fátima Roque; Maria Teresa Herdeiro (MDPI AG, 2020)
Overuse and inappropriate antibiotic prescription for respiratory tract infections (RTI) are one of the major contributors to the current antibiotic resistance problem. Guidelines provide support to prescribers for proper decision-making. Our purpose is to review the impact of prescribers' exposure to guidelines in antibiotic prescription for RTIs. A systematic review was performed searching in the scientific databases MEDLINE PubMed and EMBASE for studies which exposed prescribers to guidelines for RTI and compared antibiotic prescription rates/quality before and after the implementation, with thirty-four articles included in the review. The selected studies consisted on a simple intervention in the form of guideline implementation while others involved multifaceted interventions, and varied in population, designs, and settings. Prescription rate was shown to be reduced in the majority of the studies, along with an improvement in appropriateness, defined mainly by the prescription of narrow-spectrum rather than broad-spectrum antibiotics. Intending to ascertain if this implementation could decrease prescription costs, 7 articles accessed it, of which 6 showed the intended reduction. Overall interventions to improve guidelines adherence can be effective in reducing antibiotic prescriptions and inappropriate antibiotic selection for RTIs, supporting the importance of implementing guidelines in order to decrease the high levels of antibiotic prescriptions, and consequently reduce antimicrobial resistance.